DUSP10 constrains innate IL-33-mediated cytokine production in ST2hi memory-type pathogenic Th2 cells - Takeshi Yamamoto (Nature Portfolio, 2018)
T helper 2 (Th2) cells and type 2 innate lymphoid cells (ILC2) respond differently to interleukin-33 (IL-33) stimulation. Here the authors show that a phosphatase, Dusp10, is expressed in Th2, but not ILC2, to dephosphorylate p38 kinase, reduce GATA3 transcription factor activity, and suppress the induction of IL-5 in response to IL-33.